Impacts of Clinical and Demographical Aspects on the Duration of Pytiriasis Versicolor - M. Kharis Khamdan; Yuri Widia; Dr. Rebekah J. Setiabudi; Evy Ervianti (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Pityriasis versicolor (PV) or tinea versicolor is a superficial fungal infection characterized by macules on the skin. It is generally caused by the fungus Malassezia. PV is found throughout the world, especially in tropical countries. Generally, this infection is influenced by humidity, hyperhidrosis, and population density around the world. One of the ways to establish PV is through the KOH examination. Purpose: Evaluating the correlation between the clinical and demographic factors and the duration of illness of outpatient PV patients of the Mycology Division of Dermatology and Venereology Department at Dr. Soetomo General Academic Hospital from 2018 to 2020. Methods: This is an observational analytic study based on medical records at the outpatient clinic of Mycology Division of the Dermatology and Venereology Department of Dr. Soetomo General Academic Hospital. The data was collected in October 2021. The chi-square test is used to analyze the data in this study. Result: 216 PV patients' data was collected. Most gender was male, most age group was 20-60, most weight group was 51 – 60 kg, most regional origin was from Surabaya, and most duration of infection was <3 months. In this study, topical and systemic treatment of this disease had a significant relationship with patients' duration of illness (topical p=0.05; systemic p=0.026). Conclusion: Topical and systemic treatment of this disease has a significant relationship with the duration of illness in PV patients.